A Grid Service for the Interactive Use of a Parallel Non-rigid Registration Algorithm of Medical Images - Stefanescu, R.; Pennec, X.; Ayache, N. (Methods of Information in Medicine, 2005)
Objective: The goal of this work is to improve the usability of a non-rigid registration software for medical images.Method: We have built a registration grid service in order to use the interactivity of a visualization workstation and the computing power of a cluster.On the user side, the system is composed of a graphical interface that interacts in a complex and fluid manner with the registration software running on a remote cluster.Conclusion: Although the transmission of images back and forth between the computer running the user interface and the cluster running the registration service adds to the total registration time, it provides a user-friendly way of using the registration software without heavy infrastructure investments in hospitals. The system exhibits good performances even if the user is connected to the grid service through a low throughput network such as a wireless network interface or ADSL.
Keywords: Grid service; non-rigid registration; cluster; medical imaging